Nano-Engineered Biomimetic Optical Sensors for Glucose Monitoring in Diabetes - Sajid Rauf (Sensors, 2016)
Diabetes is a rapidly growing disease that can be monitored at an individual level by controlling the blood glucose level, hence minimizing the negative impact of the disease. Significant research efforts have been focused on the design of novel and improved technologies to overcome the limitations of existing glucose analysis methods. In this context, nanotechnology has enabled the diagnosis at the single cell and molecular level with the possibility of incorporation in advanced molecular diagnostic biochips. Recent years have witnessed the exploration and synthesis of various types of nanomaterials with enzyme-like properties, with their subsequent integration into the design of biomimetic optical sensors for glucose monitoring. This review paper will provide insights on the type, nature and synthesis of different biomimetic nanomaterials. Moreover, recent developments in the integration of these nanomaterials for optical glucose biosensing will be highlighted, with a final discussion on the challenges that must be addressed for successful implementation of these nano-devices in the clinical applications is presented.